2009
DOI: 10.1139/y09-038
|View full text |Cite
|
Sign up to set email alerts
|

Sex and hormonal influences on the nicotine-induced attenuation of isoprenaline vasodilations in the perfused rat kidney

Abstract: We previously reported that nicotine impairs betta-adrenoceptor-mediated renovascular control in male rats. Here, we investigated the roles of sex and estrogen in nicotine-betta-adrenoceptor renal interaction. The effect of nicotine on renal vasodilations caused by isoprenaline was evaluated in phenylephrine-preconstricted perfused kidneys of male and proestrus female rats in absence and presence of NG-nitro-l-arginine (l-NNA, a NOS inhibitor). The in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 42 publications
2
8
0
Order By: Relevance
“…This notion is supported by the observation that E 2 , administered within a similar time frame in OVX rats, lowered BP via a nontranscriptional activation of PI3K/Akt signaling (Wu et al, 2012). Notably, plasma E 2 levels seen in male rats after a single E 2 dose of 1 μg/kg was similar to those established in proestrus or in E 2 -treated OVX rats (El-Mas et al, 2009a). The clinical relevance of the current study is likely because comparable plasma E 2 levels exist in women (T’Sjoen et al, 2005) as well as in men with endocrine disorders (Cailleux-Bounacer et al, 2009).…”
Section: Discussionsupporting
confidence: 67%
“…This notion is supported by the observation that E 2 , administered within a similar time frame in OVX rats, lowered BP via a nontranscriptional activation of PI3K/Akt signaling (Wu et al, 2012). Notably, plasma E 2 levels seen in male rats after a single E 2 dose of 1 μg/kg was similar to those established in proestrus or in E 2 -treated OVX rats (El-Mas et al, 2009a). The clinical relevance of the current study is likely because comparable plasma E 2 levels exist in women (T’Sjoen et al, 2005) as well as in men with endocrine disorders (Cailleux-Bounacer et al, 2009).…”
Section: Discussionsupporting
confidence: 67%
“…Nicotine also cause renal vasoconstriction and damage probably via increasing levels of vasoconstrictors, such as catecholamines, vasopressin and endothelin-1 [17]–[19]. Further, nicotine impairs NOS-dependent [20] and β-adrenoceptor vasoreactivity [21], [22] These discrepant vascular effects of nicotine could be attributed to differences in vascular beds or in the dose or duration of nicotine regimens.…”
Section: Introductionmentioning
confidence: 99%
“…We have recently demonstrated that estrogen enhances the vasodilator effect of acute nicotine in the renal vasculature of female rats mainly through facilitation of NOS signaling [12]. Alternatively, acute nicotine attenuates isoprenaline vasodilations in the female renal vascular bed, an effect that is downregulated by the NO/cGMP signaling [22]. In a more recent study, we reported on the chronic effect of nicotine on renal vasodilations caused by adenosine receptor activation (NECA) and the modulation of this interaction by ovarian hormones [23].…”
Section: Introductionmentioning
confidence: 99%
“…Because a recent study implicated the A 2B R/K + channel cascade in the renal vasodilatory response elicited by the adenosine analogue N ‐ethylcarboxamidoadenosine (NECA) in intact female rats, in the present study we tested the hypotheses that: (i) chronic nicotine modifies the A 2B R/K + channel‐sensitive vasodilatory action of NECA in the renal vasculature of female rats; and (ii) the hormonal status of the female rat influences the nicotine–NECA interaction in the kidney. The latter assumption receives support from the observations that nicotine, administered acutely, causes oestrogen‐dependent reductions in renal perfusion pressure (RPP) and attenuation of β‐adrenoceptor‐mediated renal vasodilation . In the present study, we performed in vitro studies to assess the effects of 2 weeks nicotine treatment on NECA‐induced vasodilation in rat isolated perfused kidneys obtained from sham‐operated rats or ovariectomized (OVX) rats treated with or without oestrogen.…”
Section: Introductionmentioning
confidence: 87%
“…Nicotine, a key component of cigarette smoke, exerts multiple vascular effects depending on the nicotine regimen and vascular preparation used. For example, nicotine constricts the renal vasculature by: (i) increasing levels of catecholamines, vasopressin and endothelin‐1; and (ii) impairing NO synthase (NOS)‐dependent vasorelaxation and β‐adrenoceptor vasoreactivity . A contradictory vasodilatory effect for nicotine has been demonstrated in cerebral and renal vascular beds .…”
Section: Introductionmentioning
confidence: 99%